Ways To Increase the Effectiveness of Physical Education Classes in Secondary Schools - Ismoilov Sherzodbek Dilshodovich (Zien Journals, 2021)
This article discusses the importance of physical education in the development of physically strong, healthy, strong-willed and spiritually active children, physical education classes with students at school and ways and means to increase their effectiveness.
Keywords: Practice; training; physical; exercise